বাংলাদেশের হৃদয় হতে - রায়, তারাপদ, ১৯৩৬- (কলিকাতা : মিত্র ও ঘোষ পাবলিশার্স, 1998)
Autobiographical reminiscences by a Bengali author.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Roy, Tarapada, -- 1936-; Authors, Bengali -- 20th century -- Biography